Factors influencing adoption of legal technology in Malaysia - Tan, Nicholas Choi Chuan (2022)
Technology has been integrated into the legal systems in most jurisdictions in the world. Covid-19 has accelerated the adoption of legal technology by the legal profession. Many lawtech start-ups have developed tools to enhance the efficiency, save time and cost of law firms. There is a general consensus within the legal profession that there is a need to adapt to the on-going digitalisation of the legal market and the changing means of provision of legal services. However, there are several challenges faced by law firms in adopting lawtech such as costs, and security concern.